BS EN IEC 61558-2-16. Safety of transformers, reactors, power supply units and combinations thereof. Part 2-16. Particular requirements and tests for switch mode power supply units and transformers for switch mode power supply units for general applications (29th August 2019) - British Standards Institution,
No abstract available